2015
DOI: 10.1371/journal.pntd.0003433
|View full text |Cite
|
Sign up to set email alerts
|

Host-Seeking Behavior and Dispersal of Triatoma infestans, a Vector of Chagas Disease, under Semi-field Conditions

Abstract: Chagas disease affects millions of people in Latin America. The control of this vector-borne disease focuses on halting transmission by reducing or eliminating insect vector populations. Most transmission of Trypanosoma cruzi, the causative agent of Chagas disease, involves insects living within or very close to households and feeding mostly on domestic animals. As animal hosts can be intermittently present it is important to understand how host availability can modify transmission risk to humans and to charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 65 publications
1
12
1
Order By: Relevance
“…It is known that oviposition exhibits a strong circadian rhythm with a peak at the same temporal window as dispersal and search for food [ 49 ]. Although other authors did not find a clear pattern of egg-laying distribution [ 28 ], in our study all eggs were found inside and around the shelter, suggesting a particular spatial egg-laying preference, strategically localized in the opposite corner to the host.…”
Section: Resultscontrasting
confidence: 96%
See 3 more Smart Citations
“…It is known that oviposition exhibits a strong circadian rhythm with a peak at the same temporal window as dispersal and search for food [ 49 ]. Although other authors did not find a clear pattern of egg-laying distribution [ 28 ], in our study all eggs were found inside and around the shelter, suggesting a particular spatial egg-laying preference, strategically localized in the opposite corner to the host.…”
Section: Resultscontrasting
confidence: 96%
“…Nuñez [ 27 ] reported similar activity levels in R. prolixus with equivalent fasting intervals; although as the activity recording continued, and consequently starvation intensified, activity was augmented, mainly in the host presence. Castillo-Neyra et al [ 28 ] observed that host removal lead to increased T. infestans activity. However, in both mentioned studies [ 27 , 28 ], methodological differences do not allow a direct comparison with the present data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Human subject research participants provided written consent for the collection of bugs from his or her household and for human subject research. The IACUC of Universidad Peruana Cayetano Heredia is registered in the National Institutes of Health at the United States of America with PHS Approved Animal Welfare Assurance Number A5146-01 and adheres to the Animal Welfare Act of 1990 [3,39].…”
Section: Ethics Statementmentioning
confidence: 99%